Changes in oxidative stress markers in pediatric burn injury over a 1-week period - Harma Birsen; Kıran Tuğba Raika (Open Chemistry, 2023)
The importance of oxidative stress in the pathogenesis of burn injuries has been shown in various studies. Glutathione (GSH) and thiols have important roles in antioxidant protection and detoxification. The study aimed to investigate the relationship between pediatric burn trauma and GSH and thiol homeostasis. Twenty-nine children with thermal-burn injuries and 29 healthy peers are included in this prospective randomized study. Children with burn wounds of 15–25% of total body surface area (TBSA) were included in the patient group. The control group was created from healthy peers of both sexes. All children were 1–10 years of age. Serum GSH, oxidized glutathione (GSSG), redox ratio (GSH/GSSG), and thiol–disulfide (SS) tests were conducted in both groups, and the changes between admission and day 7 were analyzed in patients with burn injuries. The mean age was 4.09 ± 2.54 years for the patient group and 4.28 ± 2.55 years for the controls (p > 0.05). Total thiol (TT), native thiol (SH), and SS levels were significantly lower in the patient group than in the controls (TT = 291.69 ± 7.93 vs 346.79 ± 18.89 μmol/L, SH = 259.39 ± 7.90 vs 297.64 ± 12.81 μmol/L, SS = 16.15 ± 4.68 vs 24.58 ± 5.76 μmol/L; p < 0.001). SH/TT ratio was higher in the patient group (89.05 ± 3.00 vs 85.93 ± 3.01 μmol/L; p < 0.001). The SS/SH and SS/TT ratios were significantly lower in the patient group, while the SH/TT ratio was significantly higher (p < 0.001). The patients had significantly decreased GSH levels (26.12 ± 2.42 vs 34.80 ± 2.26) and GSH/GSSG ratios (1.69 ± 0.12 vs 3.05 ± 0.29) and increased GSSG levels (16.09 ± 0.34 vs 11.48 ± 1.17, p < 0.001 for all). The GSSG level and GSSG/SH and GSSG/TT ratios were higher in the patient group than in the controls while the SH, TT, and SS levels, and SS/SH and SS/TT ratios were lower in the patient group. Analysis of serum GSSG levels, and ratios with SH and TT homeostasis, might be useful in order to determine burn damage in children.